THE ROLE OF MEDIATION ON WORK SATISFACTION TO WORK ENVIRONMENT, TRAINING, AND COMPETENCY ON EMPLOYEE PERFORMANCE - Ingsih, Kusni; Riskawati, Nelis; Prayitno, Agus; Ali, Shujahat (Universitas Brawijaya, Indonesia, 2021)
This study aimed to determine the effect of work environment, training, and competence on work satisfaction in improving employee performance. The object in this study is PT. Asaputex Jaya, located in Tegal City, engaged in woven sarong's trading business with the Korma Tree brand. The sample used in this study was determined by a simple random sampling method, obtaining 105 respondents. The data in this study were obtained through a questionnaire that was filled out independently. The analysis used in this study uses the analysis method of Structural Equation Modeling (SEM). This study proves and concludes that: work environment and work training have a significant positive effect on work satisfaction. However, competence does not affect work satisfaction. Besides, the work environment negatively affects employee performance, and work training does not affect employee performance. Also, competence and work satisfaction have a significant positive effect on employee performance. Further research must develop more varied models to provide different research findings, such as adding work stress variables, work motivation, work discipline, and others.